1989
DOI: 10.1021/bi00434a054
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and enzymological characterization of the interaction between transcription termination factor .rho. and .lambda. cro mRNA

Abstract: Termination of transcription at tR1, the rho-dependent terminator between genes cro and cII of bacteriophage lambda, is mediated by interactions between rho protein and an RNA sequence element called rut. We show, using a filter retention assay technique, that rho protein binds with about 10-fold lower affinity to variants of cro RNA lacking both parts of rut or to normal cro RNA having one or the other part of rut bound to a complementary DNA oligonucleotide than it binds to unmodified cro RNA. These same var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…Binding to this site is a prerequisite for the activation of the ATPase activity of Rho. This is required for its subsequent helicase and transcription termination functions (14,36). Our data and previous findings suggest that the RNA sequence in the vicinity of tnaC stop codon constitutes the critical entry site for Rho.…”
Section: Discussionsupporting
confidence: 71%
“…Binding to this site is a prerequisite for the activation of the ATPase activity of Rho. This is required for its subsequent helicase and transcription termination functions (14,36). Our data and previous findings suggest that the RNA sequence in the vicinity of tnaC stop codon constitutes the critical entry site for Rho.…”
Section: Discussionsupporting
confidence: 71%
“…Rho Binds to Circular RNA-To determine whether Rho can bind the circular cro derivative RNA, we used the nitrocellulose filter-binding technique to isolate complexes of Rho with radiolabeled RNA (15,18). With saturating levels of Rho, ϳ60% of the circular cro RNA was retained on the filter.…”
Section: Resultsmentioning
confidence: 99%
“…Faus and Richardson (15) showed that blocking this portion of the rut site with an oligonucleotide inhibited Rho's ability to bind to cro RNA. Also, Chen et al (20) showed that blocking the rut site with a similar DNA oligonucleotide inhibited Rho's in vitro termination activity at the tR1 terminator of the cro gene.…”
mentioning
confidence: 99%
“…Rho carries an RNA-dependent ATPase activity that displays an RNA cofactor requirement similar to that of rho-dependent termination: i.e., a rho binding site on the RNA that is relatively devoid of stable secondary structure and relatively rich in cytosine residues. This ATPase activity and its cofactor requirements have been extensively studied (Lowery & Richardson, 1977a,b;Galluppi & Richardson, 1980;McSwiggen, 1985;von Hippel et al, 1987;Faus & Richardson, 1989). Using this RNA-dependent ATPase as an energy source, Brennan et al (1987) have shown that rho can act as a 5' 4 3' directional RNA-DNA helicase on RNA-DNA heteroduplex constructs that carry a singlestranded region of RNA at the 5' end.…”
mentioning
confidence: 99%